Elaboración de una Guía de uso Turístico del Sendero los Contrabandistas entre Las Comunidades San Pedro – El Placer de la Parroquia Río Verde, Cantón Baños de Agua Santa. - Hidalgo Calderón, Gabriela Dayanara (2019)
the project proposed a guide for the promotion and tourist use of the smuggler's path between the San Pedro - el placer communities in the río verde parish of the Baños de Agua Santa canton, for which an environmental, socioeconomic diagnosis of the canton and parish, of in the same way, the current situation of the trail was analyzed by carrying out a registry of the natural resources it possesses, through the use of tokens issued by the ministry of tourism (mintur), for a hierarchy of them, in the same way the current conditions on the tourist services that the community has in what refers to tourist plant, thus increasing the tourist diffusion of the community.